Claiming the people's past : populist politics of history in the twenty-first century - Bevernage, Berber Herausgeber (Metamorphoses of the political: multidisciplinary approaches, 2025)
"This volume offers the first global and systematic overview of populist politics of history in the twenty-first century. An international group of scholars interrogates how and why populists engage with the past. Twelve case studies focus on uses of history and memory by populist movements across the globe - ranging from Brazil to Bangladesh, from Poland to Tanzania. Five thematic chapters zoom in on key features of populism: its relation to time, nationalism, emotions, academic expertise, and the language of 'moral remembrance'. The focus is both on left- and right-wing populism, as well as on oppositional populism and populists in power. This way, the volume presents an empirically rigorous and conceptually innovative analysis of populist historical reason"--